SYNTHESIS AND CHARACTERIZATION OF GREEN METALLIC SILVER NANOPARTICLES USING AQUEOUS EXTRACT OF SETARIA VERTICILLATA AND ASSESSING ITS ANTIMICROBIAL ACTIVITY - A. PRABHU; K. SHANKAR; P. MUTHUKRISHNAN; K. PRABHAKARAN (International Journal of Pharma and Bio Sciences, 2015)
In this work, we reported synthesized silver nanoparticles using the aqueous extract of Setaria verticillata and assessing its antimicrobial activity. The synthesized silver nanoparticles were characterized by UV-Visible spectrophotometry, FT-IR spectroscopy, Scanning electron microscopy and Energy dispersive X-ray analysis. The antimicrobial activity was assessed using agar well diffusion method. The average particle’s size of synthesized silver nanoparticles was 12 ± 4 nm. EDAX analysis confirmed the presence of silver nanoparticles Ag (83.02 %). The antimicrobial activity study reveals that the maximum zone of inhibition was observed in Pseudomonas aeruginosa and lowest inhibition activity was found in Escherichia coli.The results indicated that Setaria verticillata mediated silver nanoparticles can be synthesized by green chemistry and eco-friendly approach.